Human Resource Management in Public Sector Policy Implementation (A Case Study of Sanitary Landfill Operations in Malang City) - I Made Arie Widyasthana Wartana Putra; Denny Iswanto (Institut Pemerintahan Dalam Negeri, 2025)
The sanitary landfill system has become a critical strategy for urban waste management to minimize environmental risks and ensure sustainable public service delivery. However, the effectiveness of this policy largely depends on the capacity and performance of public sector human resources as the primary implementers. This study examines the role of public sector human resource management (HRM) in supporting the implementation of sanitary landfill operations at the Supit Urang Final Disposal Site (TPA) in Malang City, Indonesia. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and document analysis involving key informants such as the UPT head, administrative staff, heavy-equipment operators, and landfill workers. Informants were selected purposively. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. Findings indicate that the effectiveness of sanitary landfill implementation is significantly influenced by the capacity of human resources, including uneven technical competency, high workloads, and limited formal training. Employee motivation was found to be low due to the absence of incentives and performance-based rewards, affecting the consistency of SOP implementation. Furthermore, leadership practices characterized by informal communication and irregular supervision contributed to gaps between standard procedures and actual practices in the field. The study concludes that public sector HRM plays a decisive role in the successful implementation of sanitary landfill policies. Strengthening HR capacity through technical training, incentives, structured communication, and routine supervision is essential to ensure consistent and sustainable policy implementation.